The infrared–radio correlation of spheroid- and disc-dominated star-forming galaxies to z ∼ 1.5 in the COSMOS field. Issue 1 (14th December 2017) - Molnár, Dániel Cs; Sargent, Mark T; Delhaize, Jacinta; Delvecchio, Ivan; Smolčić, Vernesa; Novak, Mladen; Schinnerer, Eva; Zamorani, Giovanni; Bondi, Marco; Herrera-Ruiz, Noelia; Murphy, Eric J; Vardoulaki, Eleni; et al.
Abstract: Using infrared data from the Herschel Space Observatory and Karl G. Jansky Very Large Array 3 GHz observations in the COSMOS field, we investigate the redshift evolution of the infrared–radio correlation (IRRC) for star-forming galaxies (SFGs) we classify as either spheroid- or disc-dominated based on their morphology. The sample predominantly consists of disc galaxies with stellar mass ≳ 10 10 M⊙, and residing on the star-forming main sequence (MS). After the removal of AGN using standard approaches, we observe a significant difference between the redshift evolution of the median IR/radio ratio $\overline{q}_{TIR}$ of (i) a sample of ellipticals, plus discs with a substantial bulge component ('spheroid-dominated' SFGs) and, (ii) virtually pure discs and irregular systems ('disc-dominated' SFGs). The spheroid-dominated population follows a declining $\overline{q}_{TIR}$ versus z trend similar to that measured in recent evolutionary studies of the IRRC. However, for disc-dominated galaxies, where radio and IR emission should be linked to star formation in the most straightforward way, we measure very little change in $\overline{q}_{TIR}$ . This suggests that low-redshift calibrations of radio emission as a star formation rate (SFR) tracer may remain valid out to at least z ≃ 1–1.5 for pure star-forming systems. We find that the different redshift evolution of q TIR for the spheroid- and disc-dominated sample is mainly due to an increasing radio excess for spheroid-dominated galaxies at z ≳ 0.8, hinting at some residual AGN activity in these systems. This finding demonstrates that in the absence of AGN, the IRRC is independent of redshift, and that radio observations can therefore be used to estimate SFRs at all redshifts for genuinely star-forming galaxies.